2014
DOI: 10.2138/am.2014.4775
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of K-dominant tourmaline

Abstract: K-dominant tourmaline was synthesized in the system MgO-Al 2 O 3 -B 2 O 3 -SiO 2 -KCl-H 2 O at 700 °C and 4.0 GPa. The crystals were zoned and characterized by less-potassic cores (1.46 wt% K 2 O) and more-potassic rims (up to 3.44 wt% K 2 O). The K-dominant tourmaline rims are represented by the average structural formula (K 0.60(3) o 0.36(3) )(Mg 2.60(7) Al 0.40(7) )(Al 5.98(3) Si 0.02(3) )Si 6 O 18 (BO 3 ) 3 (OH) 3.92(7) O 0.08(8) , which is analogous to the structural formula of dravite and is referred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 17 publications
1
6
0
2
Order By: Relevance
“…Any nitrogen-bearing fluid-rock system at sufficiently reducing conditions may contain or produce NH 4 , which, due to its similar ionic radius to Rb, may to certain extent replace the larger monovalent cations such as K, in most silicate structures, particularly in micas and K-feldspar. In contrast, experiments by Berryman et al (2014;and in prep. ) have shown that significant K-incorporation into tourmaline is restricted to high-pressure conditions and K-rich, Na-poor bulk compositions.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Any nitrogen-bearing fluid-rock system at sufficiently reducing conditions may contain or produce NH 4 , which, due to its similar ionic radius to Rb, may to certain extent replace the larger monovalent cations such as K, in most silicate structures, particularly in micas and K-feldspar. In contrast, experiments by Berryman et al (2014;and in prep. ) have shown that significant K-incorporation into tourmaline is restricted to high-pressure conditions and K-rich, Na-poor bulk compositions.…”
Section: Discussionmentioning
confidence: 89%
“…The solid starting material consisted of a homogeneous mixture of SiO 2 , γ-Al 2 O 3 , MgO, and H 3 BO 3 in the stoichiometric proportions of end-member dravite, NaMg 3 Al 6 Si 6 O 18 (BO 3 ) 3 (OH) 4 , without any sodium, and with excess SiO 2 and H 3 BO 3 . Following the method of tourmaline synthesis from previous studies (Von Goerne and Franz 2000;Meyer et al 2008;Berryman et al 2014) we used excess boric acid in double of the stoichiometric amounts, and excess SiO 2 by 20 mol% to compensate for high fluid solubility of these components. About 15 mg of the solid starting material was loaded into a welded gold capsule 10 mm in length and 3 mm in diameter together with ~3 mg of a 25% NH 4 (OH) solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the finding of microdiamond inclusions in K‐rich tourmaline from the Kokchetav massif, Shimizu and Ogasawara suggested that the incorporation of K in the tourmaline structure can extend its stability field up to 6 GPa and 1000°C. A successful synthesis of K‐rich tourmaline has been achieved at 4 GPa and 700°C, which also upheld its high‐pressure origin.…”
Section: Introductionmentioning
confidence: 84%
“…Воскресенской, являются очень высокие Р−Т-параметры и высококонцентрированные растворы, требующие использования дорогостоящего оборудования и материалов. В работе (Goerne et al, 1999) Rosenberg, Foit, 1986;Ekambaram, 1986;Schreyer et al, 2000;Marler et al, 2002;Ertl et al, 2012;Kutzschbach et al, 2017 Rosenberg, Foit, 1986;Ekambaram, 1986;Lynch, 1997;Goerne et al, 1999 Dutrow et al, 1999, Ertl et al, 2012Berryman et al, 2015Berryman et al, , 2016 CaO Воскресенская, иванова, 1975;Taran et al, 1993;Setkova et al, 2011;London, 2011;Рождественская и др., 2012Рождественская и др., , Vereshchagin et al, 2015 ЭКсПеРиМенТАльнОе изучение усТОйчиВОсТи ГЕОХИМИЯ №10 2019 сеТКОВА, БАлицКий, ШАПОВАлОВ и в особенности давлениях до 4 ГПа (Berryman et al, 2014(Berryman et al, , 2016.…”
unclassified